Methodology for Mechanical Characterization of Soft Biological Tissues: Arteries. (2015) - G., A.I. Arroyave; Lima, R.G.; Martins, P.A.L.S.; Ramião, N.; Jorge, R.M.N.
Abstract: Several methods and types of mechanical tests have been used to estimate the mechanical properties of soft biological tissues such as arteries. The load environment that an artery is subjected can be simulated in vitro through biaxial tensile tests. For this, many procedures have been used to characterize this kind of tissue, and therefore there is no standardization of these procedures. In this study, a methodology for testing and data processing has been proposed and tested. Biaxial tensile testing for three groups of arteries: abdominal aorta, thoracic aorta and left subclavian were performed at the Biomechanics Laboratory of INEGI, University of Porto (FEUP) to assess the methodology. The samples were tested up to the rupture. Stress-strain curves in the axial and circumferential axes were obtained and showed the nonlinear hyper-elastic behavior of the arteries. The limit to rupture and the elastic limit were estimated. Analyzing the mechanical behavior of both axis and making a comparison between them, it can be concluded that the axial axis shows greater resistance on average for all sample groups. The two-dimensional model of Strain Energy Function for hyper-elastic materials proposed by Fung and the bilayer model proposed by Holzapfel, both derived from the continuum mechanics, were used to perform a fitting of the experimental data, and predict the tissue behavior under different stresses or strains. The high coefficients of correlation between the experimental and fitted curves indicate that both models can model the pig arterial tissue. Histological analyses of the samples were performed in order to estimate the average content of collagen and elastin in the tissue. A high percentage of elastin was observed in all sample groups. The result of this work is a description and an implementation of a methodology for the characterization of soft biological tissues.